Causal associations and potential mechanisms between inflammatory skin diseases and IgA nephropathy: a bi-directional Mendelian randomization study - Cao, Wenlong; Xiong, Jing (Frontiers in Genetics, 2024)
Background There is growing evidence of an association between inflammatory skin diseases and chronic kidney disease, but the association between inflammatory skin diseases and IgA nephropathy has rarely been studied. Thus, bi-directional Mendelian randomization was employed to explore the causality between inflammatory skin diseases (including atopic dermatitis, acne and psoriasis) and IgA nephropathy. Methods The selection of instrumental variables for inflammatory skin diseases and IgA nephropathy were based on genome-wide association studies. Following the heterogeneity and pleiotropy tests, the bidirectional causality was evaluated by inverse variance weighted along with four other approaches. Three atopic dermatitis-related datasets were obtained from the GEO database and then combined. In the combined dataset, the expression of galactose-deficient IgA1-associated genes (including GALNT2, GALNT12, C1GALT1, C1GALT1C1 and ST6GALNAC2) were compared between atopic dermatitis patients and healthy controls. Results Atopic dermatitis was associated with an increased risk of IgA nephropathy (OR = 1.054, 95% CI = 1.014–1.095, p = 0.007). However, acne and psoriasis showed no significant causal relationship with IgA nephropathy (OR = 0.988, 95% CI = 0.948–1.031, p = 0.583; OR = 0.996, 95% CI = 0.966–1.028, p = 0.821). In the combined microarray dataset, the expression levels of GALNT12 and C1GALT1C1 in atopic dermatitis patients were significantly lower compared with controls (p = 2.3e−9; p = 0.00067), which may contribute to an increase in aberrant IgA1 synthesis. Conclusion Among inflammatory skin diseases, atopic dermatitis was found to increase the risk of IgA nephropathy, which may result from the decrease of GALNT12 and C1GALT1C1 expression and the increase of aberrant IgA1 production. Therefore, active management of atopic dermatitis may help prevent the occurrence and progression of IgA nephropathy.